Concentracion foliar de nitrogeno, fósforo y potasio en plantaciones forestales de Simarouba amara Aubl “Marupa” y Vochysia lomatophylla “Quillosisa” en Puerto Almendra, Loreto-Perú, 2023 - Del Aguila Caiña, Pablo David (2025)
The study was conducted at the Puerto Almendra Forestry Research and Teaching Center (CIEFOR) of the National University of the Peruvian Amazon (UNAP). It is located on the right bank of the Nanay River, 22 km southwest of the city of Iquitos. Geographically, it is located at the coordinates 3° 49´ 40´´ south latitude and 73° 22´ 30´´ west longitude, at an altitude of approximately 122 meters above sea level. It belongs to the District of San Juan Bautista, Province of Maynas, Loreto Region (UNAP, 2019). The objective was to determine the foliar concentration of nitrogen, phosphorus and potassium in forest plantations in Puerto Almendras, Loreto, Peru, 2023, finding that the average concentration of Nitrogen (N) 1,925%, Phosphorus (P) 0,075% and Potassium (K) 0.5225% in forest plantations of Simarouba amara Aubl “marupa” and for Vochysia lomatophylla “quillosisa”, Nitrogen (N) 1,63%, Phosphorus (P) 0,075% and Potassium (K) 0,4875%; this shows that they do not present nutritional deficiencies, they are within the established ranges of sufficiency for Nitrogen the range is 1 to 3%, in Phosphorus it is 0,05 to 1,0% and Potassium is 0,30 to 3,0%. For proper plant development, these values must be within the range of sufficiency; an excess or deficit causes anomalies in plant development.